Comparative analysis of quality indicators and regulatory compliance of milk in different rural properties in the municipality of Aparecida, state of Paraíba (PB), Brazil (Research, Society and Development, 2025)
This study aimed to analyze the quality of milk produced in different rural properties in the municipality of Aparecida, PB, comparing indicators such as pH, acidity, density, fat content, and cryoscopy, and verifying compliance with regulations established by the Ministry of Agriculture. The research involved collecting milk samples from five producers over a period of 30 days, with physico-chemical analyses conducted in triplicate. The results indicated that most producers met the parameters required by legislation, with producer P1 standing out for presenting better results in acidity and density, reflecting proper management and refrigeration practices. However, variations were observed in some parameters, such as acidity and density, suggesting that adopting more rigorous temperature control and feeding practices could improve milk quality. The study contributes to understanding the variability in local milk production and reinforces the importance of implementing good practices to ensure compliance with sanitary standards and food safety.